Hypoxia Induces Macrophage tnfa Expression via Cyclooxygenase and Prostaglandin E2 in vivo - Lewis, Amy; Elks, Philip M. (Frontiers in Immunology, 2019)
Macrophage phenotypes are poorly characterized in disease systems in vivo. Appropriate macrophage activation requires complex coordination of local microenvironmental cues and cytokine signaling. If the molecular mechanisms underpinning macrophage activation were better understood, macrophages could be pharmacologically tuned during disease situations. Here, using zebrafish tnfa:GFP transgenic lines as in vivo readouts, we show that physiological hypoxia and stabilization of Hif-1α promotes macrophage tnfa expression. We demonstrate a new mechanism of Hif-1α-induced macrophage tnfa expression via a cyclooxygenase/prostaglandin E2 axis. These findings uncover a macrophage HIF/COX/TNF axis that links microenvironmental cues to macrophage phenotype, with important implications during inflammation, infection, and cancer, where hypoxia is a common microenvironmental feature and where cyclooxygenase and TNF are major mechanistic players.